Contextual and Individual Determinants of Anterior Open Bite in Adolescents - Bastos Roosevelt-Silva; Pistelli Gustavo-Chab; Ferreira Fernando-Pedrin-Carvalho; Bastos José-Roberto-Magalhães; Janson Guilherme; Ferreira Raquel-Conceição (International Dental Journal, 2023)
Objective: Studying the broader determinants of anterior open bite (AOB) may guide more equitable policies.This study estimates the prevalence of AOB in Brazilian adolescents and its association with contextual and individual determinants. Methodology: The data for dentofacial anomalies in 15- to 19-year-olds from the National Oral Health Survey SBBrasil 2010 were analysed (N = 4748). AOB was based on the Dental Aesthetic Index (AOB = 0; AOB > 0); the contextual variables were the Human Development Index (HDI) and the Gini Index (2010). The individual sociodemographic variables included sex (male, female), self-reported skin colour/race (white, black, brown, and indigenous + yellow), family income (≥4 minimum wage [MW]; 0–3 MW), and educational attainment (ideal, delayed). The individual clinical variables were decayed, missing, and filled teeth (DMFT) (0, ≥1), first permanent molar loss (0, ≤3, 4), and molar relationship (normal, half cusp, full cusp). Multilevel logistic regression models with random intercepts and fixed slopes were used to estimate odds ratios (ORs) and confidence intervals (95% CIs). Results: AOB prevalence in Brazil was 8.78% (95% CI, 6.85–11.20) at 15 to 19 years of age. The lowest prevalence was in São Luis (2.63%; 95% CI, 0.58–11.03) and the highest was in João Pessoa (29.85%; 95% CI, 15.93–48.85), both capitals of the northeast Brazilian region. A higher prevalence of AOB (OR, 1.71; 95% CI, 1.04–2.80) was observed in municipalities with a lower HDI. Adolescents who declared their skin colour black, with lower family income, with delayed education, with DMFT ≥ 1, who lost 4 permanent first molars, and who had a complete molar cusp relationship were more likely to have AOB. Conclusions: AOB varied amongst Brazilian municipalities. The HDI plays an important role in the prevalence of AOB; individual social determinants have also been associated with AOB malocclusion in adolescents.